Resilience of the Urban Poor Daring the Covid-19 Pandemic - Ernawati S. Kaseng (Rayhan Intermedia, 2022)
This study aims to describe the living conditions of the urban poor during the Covid-19 pandemic in Makassar City. The research method in this study uses a descriptive-qualitative approach. Data collection techniques were carried out through observation, interviews and documentation. The data validation technique is triangulation of sources to assess the credibility of data from data sources. Data analysis techniques through data reduction, data presentation, and conclusions. The results of the study show that changes in behavior and the impact on economic activity during the Covid-19 pandemic have led to an increase in the number and level of poverty in Makassar City. This can be seen from the decrease in income due to increased unemployment and reduced employment and business opportunities. For this reason, the government has implemented a short-term and fast management program in the form of a social safety net to overcome health, economic and social shocks caused by the Covid 19 pandemic through several assistance policies to the urban poor in particular and society in general.